Instrumental Procedures for the Evaluation of Juiciness in Peach and Nectarine Cultivars for Fresh Consumption - Paola Baltazar; Eva Cristina Correa; Belén Diezma (Agronomy, 2020)
There is growing interest within the peach and nectarine markets in obtaining and selling ready-to-eat fruits. For this, pre-ripening protocols are being applied, which do not always result in sufficiently juicy fruits. Therefore, the aim of this study is the development of objective instrumental procedures for quantification of the juiciness attributes of these fruits. In this work, we evaluated the juiciness of more than 2000 fruits belonging to 20 of the varieties of greatest interest in the southeast of Spain. An instrumental mechanical procedure based on the confined compression of a pulp specimen of known volume was designed and optimized. Instrumental juiciness was defined as the wet area (cm2) on an absorbent paper located under the compression probe. This test allowed for the defining of objective thresholds for the identification of juicy fruits; 90% of the fruits with areas higher than 5.4 cm2 were considered to be juicy. Complementarily, non-invasive supervision by near-infrared (NIR) spectroscopy, based on pulp structural changes during ripening, allowed for estimation of the instrumental juiciness with coefficients of correlation above 0.83. The results of these instrumental procedures contribute to supporting decision tools in the logistics chain of stone fruits.